The Word, Prophecy, Time, Blessing: A Thematic Itinerary through Genesis 1 - Mazzinghi, Luca (Ghana journal of religion and theology, 2022)
The article proposes a thematic reading of the first chapter of Genesis, through the analysis of three words: Word, Time, and Blessing. The aim is to show how the narrative, located in the period of the Babylonian exile, was not intended to offer a nostalgic reading of the origins, but to offer meaning to the present, a complex present, difficult but open to God's surprises. Because of this dynamism, the text also speaks to our contemporaneity, often steeped in sadness and lack of meaning, offering our generation the image of the divine dream of a world governed by the gentleness of the 'word.’